Navigating the Honey Markets Across Europe and Africa - (:unkn) unknown (My University, 2024)
India ranks fourth globally in terms of honey export but the Indian honey was mainly exported to American and Asian continent consisting of over 85 per cent of total honey exported by India leaving huge untapped potential in Europe which is second largest importer of honey worldwide as well as Africa. Keeping this in mind an analysis of European and African honey market was done using secondary data and results were interpreted in excel sheet. It was found that European honey production was primarily led by Spain. The continent accounted for approximately 45 per cent of global honey imports, with Germany being the largest importer with imported value of 306674.7 thousand USD (2023). India shared less than 0.1 per cent of total European honey imports. It was also observed that Africa contributed to 10 per cent of the world's total honey output. The continent’s honey import was considerably lower than global imports. In terms of export, Egypt led African honey exports. India shared only 12 per cent of total honey imports to Africa. It was noted that both Europe and Africa presented huge untapped potential for Indian honey. It was suggested to improve post harvest management of honey for maintaining quality standards and government support for increasing exports to the continents.
Keywords: African Research